Emotion Regulation Difficulties Moderate the Association Between Typical Drinking and Sexual Assault Victimization Among Sexual and Gender Minority University Students - Kirwan, Mitchell (Violence against women, 2024)
Sexual and gender minority (SGM) students report higher alcohol consumption, emotion regulation difficulties, and sexual assault victimization severity than cisgender, heterosexual individuals. A sample of 754 undergraduate students completed an online survey assessing alcohol use, emotion regulation, and sexual victimization. Regression analyses indicated that, among SGM students with higher emotion regulation difficulties, typical weekly drinking was positively associated with sexual assault victimization severity, but among cisgender, heterosexual students and SGM students with lower emotion regulation difficulties, there was no association between drinking and victimization severity. Thus, SGM students benefit from interventions targeting alcohol use and emotion regulation difficulties.